Upaya Pelestarian Wayang Potehi Di Tengah Modernisasi Pada Masyarakat Tionghoa Kota Semarang - Alba Nafi’ah Kurniasanti; Margareta Puttri Edenia; Tirta Perwita Sari; Fauzan Syahru Ramadhan (Badan Riset dan Inovasi Nasional (BRIN), 2025)
This article focuses on the preservation of Wayang Potehi amidst the modernization of the Chinese community in Semarang City. This research aims to analyze in depth the efforts to preserve Wayang Potehi as a traditional performing art that has become the cultural identity of the Chinese community in Semarang City, amidst the current modernization and changes in the lifestyle of the younger generation, and the existence of Wayang Potehi which faces serious threats. The methods used in this article are observation and history, which include heuristics, source criticism, interpretation, and historiography, as well as data collection through interviews with puppeteers, temple administrators, and art community members, accompanied by direct observation of performances and studio activities. The results show that the main challenge of Wayang Potehi preservation lies in the lack of regeneration of puppeteers and puppet craftsmen, as well as the lack of interest of the younger generation. However, a number of strategies have been implemented, such as regular training, the active role of the Tek Gie Hien studio, cooperation with the temple, and the use of digital media as a means of promotion and education. This study concludes that the preservation of Wayang Potehi requires collaboration between local communities, cultural institutions and technology to remain relevant in the modern era.